2020
DOI: 10.2478/rjim-2020-0016
|View full text |Cite
|
Sign up to set email alerts
|

Medication use and polypharmacy in patients referred to a tertiary gastroenterology practice

Abstract: AbstractIntroduction: Commonly prescribed medications are associated with various gastrointestinal (GI) side effects but few data are available on prescription medication use and polypharmacy in a gastroenterology outpatient practice. We aimed to examine the prevalence of polypharmacy, defined as the simultaneous use of 5 or more medications.Methods: A descriptive correlational study of consecutive outpatient consul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Al-Hashar et al [ 7 ] in Oman and Al-Amin et al [ 8 ] in Bangladesh have shown that among CVDs patients, drugs related to the alimentary tract and metabolism were the most frequently used after cardiovascular medications. One possible explanation for this may be the use of different medicines in patients with CVDs which makes it inevitable to use antacid drugs to control the GI upset caused by simultaneous consumption of other medications [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Al-Hashar et al [ 7 ] in Oman and Al-Amin et al [ 8 ] in Bangladesh have shown that among CVDs patients, drugs related to the alimentary tract and metabolism were the most frequently used after cardiovascular medications. One possible explanation for this may be the use of different medicines in patients with CVDs which makes it inevitable to use antacid drugs to control the GI upset caused by simultaneous consumption of other medications [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“… 86 Other common gastrointestinal symptoms including dyspepsia are also frequently associated with polypharmacy. 87 , 88 …”
Section: Polypharmacy and Medication Side Effectsmentioning
confidence: 99%